2015
DOI: 10.1038/nature14621
|View full text |Cite
|
Sign up to set email alerts
|

Beating the Stoner criterion using molecular interfaces

Abstract: It is accepted that only three elements are ferromagnetic at room temperature, the transition metals iron, cobalt and nickel. The Stoner criterion explains why, for example, iron is ferromagnetic but manganese is not, even though both elements have an unfilled 3d shell and are adjacent in the periodic table: the product of the density of states with the exchange integral must be greater than unity for spontaneous ordering to emerge.1,2 Here, we demonstrate that it is possible to alter the electronic states of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

13
184
1
1

Year Published

2016
2016
2019
2019

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 170 publications
(202 citation statements)
references
References 38 publications
13
184
1
1
Order By: Relevance
“…The effect has been reported for a variety of molecules on ferromagnetic substrates as well as for graphene [Dedkov 2008, Dzemiantsova 2011, Mandal 2014, Marchenko 2015, Weser 2010, Weser 2011, Usachov 2015, also on ferromagnetic substrates. This trend towards an induced polarization in the adlayer may be rationalized in terms of the Stoner criterion [Ma'Mari 2015], and induced polarization from proximity effects is well described by mean field arguments [Dowben 1991, Mathon 1986, Schwenk 1998]. …”
mentioning
confidence: 90%
“…The effect has been reported for a variety of molecules on ferromagnetic substrates as well as for graphene [Dedkov 2008, Dzemiantsova 2011, Mandal 2014, Marchenko 2015, Weser 2010, Weser 2011, Usachov 2015, also on ferromagnetic substrates. This trend towards an induced polarization in the adlayer may be rationalized in terms of the Stoner criterion [Ma'Mari 2015], and induced polarization from proximity effects is well described by mean field arguments [Dowben 1991, Mathon 1986, Schwenk 1998]. …”
mentioning
confidence: 90%
“…Charge transfer and d(metal)-π(carbon) orbital coupling at the interface may change the density of states, spin population, and exchange of metallocarbon interfaces (4,15,16). The interaction between the molecule and the metal depends strongly on the morphology and specific molecular geometry (17, 18).…”
mentioning
confidence: 99%
“…In particular, the fine-tuning of spin polarization at metallo-organic interfaces opens a realm of possibilities, from the direct applications in molecular spintronics and thin-film magnetism to biomedical imaging or quantum computing. This interaction at the surface can control the spin polarization in magnetic field sensors, generate magnetization spin-filtering effects in nonmagnetic electrodes, or even give rise to a spontaneous spin ordering in nonmagnetic elements such as diamagnetic copper and paramagnetic manganese (1)(2)(3)(4)(5)(6)(7)(8)(9)(10)(11).…”
mentioning
confidence: 99%
“…This approach, which has been coined "spinterface science" [57,88], has become a very active field of research. It has been shown that, due to orbital hybridization, the spin polarization at ferromagnetic surfaces may be amplified or inverted [57,89], spin-filtering tunneling may occur at molecular adsorbate sites [90], and non-magnetic metallic layers may even become ferromagnetic upon interface formation with carbon-based molecules [91]. In addition, interfacial magnetoresistance due to a single ferromagnetic/molecular interface has been demonstrated [92].…”
Section: Spin Dependent Effects At Hybrid Interfacesmentioning
confidence: 99%
“…Very recently, it was demonstrated that even for nonmagnetic metals, Cu and Mn, magnetism may emerge due to interfaces with C 60 molecules [91]. Magnetic hysteresis was observed at room temperature in C 60 /Cu and C 60 /Mn stacks using magnetometry.…”
Section: Spin Dependent Effects At Hybrid Interfacesmentioning
confidence: 99%